Selectividad de la calidad de antisueros y medios de reacción, empleados en la realización de las pruebas inmunohematológicas, mediante la titulación de la intensidad de reacción, al enfrentarlos con muestras de sangre y plasma de los hemoderivados que oferta, el servicio de medicina transfusional del hospital general docente de riobamba, durante el período noviembre 2012 – abril 2013 - Castillo Cuadrado, Evelyn Viviana (2013)
The research topic entitled "Selectivity antisera quality and reaction media employed in the embodiment of immunohematology testing by titration of the reaction strength , to face them with blood samples and blood plasma of that bid, Transfusion Medicine Service General Teaching Hospital of Riobamba , during the period November 2012 - April 2013"was held for the purpose of employing suitable reagents for immunohematology testing which ensures the reliability of the tests to evaluate the reaction antigen - antibody, for which was made different variations in techniques, the same as will be detailed in order to know them well and apply them correctly.